A study of flow in alluvial channels: depth-discharge relations - Simons, Daryl B., author; Richardson, E. V. (Everett V.), 1924-, author; Colorado State University, publisher (Colorado State University. Libraries, 1959)
Alluvial channel stage-discharge and depth-discharge relations were studied in a large sand bed-recirculating flume. From this study, it was found that the form of these relationships are intimately related to: 1. Regime of flow; 2. Form of bed roughness, a. Characteristics of the bed material, b. Concentration of fine sediment, c. Temperature; 3. Rate of change of discharge with time. In the range of shear where ripples and dunes develop on the bed, the stage-discharge curve for a rising stage is usually quite different from that for a falling stage. These curves are only valid for the conditions upon which they are based--no general solution is possible. In the range of shear, which develops plane bed, standing sand, and water waves, which are in phase, and antidunes, the rising and falling stage curves coincide and hold for all values of discharge associated with these forms of bed roughness. When a channel experiences a shear stress, which develops dunes at small discharges and plane bed and perhaps standing waves and antidunes at larger discharges, there is a discontinuity in the stage-discharge or depth-discharge curves particularly on the rising stage, which occurs when the dunes wash out. This is caused by the large reduction in resistance to flow, which occurs when the bed form changes from ripples or dunes to plane bed, standing waves, or antidunes, and the resultant reduction in depth even though discharge is increasing.
CER59DBS34.
Keywords: Alluvial streams; Streamflow velocity; Fluid dynamics